Intermetallic Compound And Reliability Study Of Sac And Snbi Lead Free Solders - Wahab, Abdul Karim Abdul (2011)
Due to the environmental concern for lead toxicity, the use of lead-free solder has been widespread in electronic packaging industries. In order for lead-free solder to replace the current lead solder, lead-free solder should have as close melting point as lead solder (1830C) and also has good wettability, excellent physical and mechanical properties. This thesis is devoted to the research and development of lead-free Sn-Bi and SAC based solder alloy for microelectronic packaging applications. A systematic study was conducted on the solders characteristics, wetting behavior, the interfacial reaction, mechanical properties and growth kinetics of solders on Cu and Ni-P substrate.